The Golden Role of the Islamic Students Association (HMI) in the Development of Democracy in Indonesia - Rudiyansah, Muhammad Mas Davit Herman (Abdurrauf Social Science, 2024)
Indonesian political history records the transition from authoritarian rule to a civil democracy system after the fall of President Soeharto on May 21, 1998. This change, which marked the end of the New Order regime and entered the Reformation Era, brought significant changes in national politics, including political liberalization. This study aims to analyze the role of the Islamic Student Association (HMI) in the development of democracy in Indonesia. HMI, as one of the largest and most historic student organizations, has contributed significantly to political education, public policy formation, leadership development, and social movements. The methodology used is a normative legal approach with secondary data analysis. This study includes a literature review, analysis of legal documents, and relevant library materials to evaluate HMI's contribution to democratic principles. Secondary data, including laws, regulations, and related literature, are used to analyze how HMI applies democratic norms in practice. Content and normative analysis are conducted to assess the relevance and impact of HMI's role. The results of the study indicate that HMI plays a strategic role in political education by increasing political awareness and student participation. In addition, HMI is also actively involved in the formation of public policy and leadership development, and plays a role in social movements such as the 1998 reform. Despite facing challenges related to independence and relevance amidst global change, HMI has managed to maintain its role as an important platform in democracy. The conclusion of this study confirms that HMI is an important pillar in the development of democracy in Indonesia. Through its contributions to political education, policy formation, and leadership development, HMI plays a significant role in shaping the socio-political dynamics of Indonesia. Although challenges remain, HMI must continue to adapt to changing times and remain focused on the core values ??and goals of the organization to continue to contribute to the progress of the nation. Keywords: Islamic Students Association (HMI); Indonesian democracy; role of organizations; democratic development. Abstrak: Sejarah politik Indonesia mencatat peralihan dari pemerintahan otoriter ke sistem demokrasi sipil pasca-kejatuhan Presiden Soeharto pada 21 Mei 1998. Perubahan ini, yang menandai akhir rezim Orde Baru dan memasuki Era Reformasi, membawa perubahan signifikan dalam politik nasional, termasuk liberalisasi politik. Penelitian ini bertujuan untuk menganalisis peran Himpunan Mahasiswa Islam (HMI) dalam pengembangan demokrasi di Indonesia. HMI, sebagai salah satu organisasi mahasiswa terbesar dan bersejarah, telah berkontribusi secara signifikan dalam pendidikan politik, pembentukan kebijakan publik, pengembangan kepemimpinan, dan gerakan sosial. Metodologi yang digunakan adalah pendekatan yuridis normatif dengan analisis data sekunder. Penelitian ini mencakup kajian literatur, analisis dokumen hukum, serta bahan pustaka yang relevan untuk mengevaluasi kontribusi HMI terhadap prinsip-prinsip demokrasi. Data sekunder, termasuk undang-undang, peraturan, dan literatur terkait, digunakan untuk menganalisis bagaimana HMI menerapkan norma-norma demokrasi dalam praktiknya. Analisis konten dan normatif dilakukan untuk menilai relevansi dan dampak peran HMI. Hasil penelitian menunjukkan bahwa HMI memainkan peran strategis dalam pendidikan politik dengan meningkatkan kesadaran politik dan partisipasi mahasiswa. Selain itu, HMI juga terlibat aktif dalam pembentukan kebijakan publik dan pengembangan kepemimpinan, serta berperan dalam gerakan sosial seperti reformasi 1998. Meskipun menghadapi tantangan terkait independensi dan relevansi di tengah perubahan global, HMI berhasil menjaga perannya sebagai platform penting dalam demokrasi. Kesimpulan penelitian ini menegaskan bahwa HMI merupakan pilar penting dalam pembangunan demokrasi di Indonesia. Melalui kontribusinya dalam pendidikan politik, pembentukan kebijakan, dan pengembangan kepemimpinan, HMI berperan signifikan dalam membentuk dinamika sosial-politik Indonesia. Meski tantangan tetap ada, HMI harus terus beradaptasi dengan perubahan zaman dan tetap fokus pada nilai-nilai inti serta tujuan organisasi untuk terus berkontribusi pada kemajuan bangsa. Kata Kunci: Himpunan Mahasiswa Islam (HMI); demokrasi Indonesia; peran organisasi; pembangunan demokrasi.